Can complaining modify a smoking environment a study on the effects of complaining on smoking behavior in different bars using agent-based model implementation - Macusi, Edison D.; Fisscher, Gerardus J.M. (2013)
In spite of the smoking ban that has been implemented in several European Union countries such as Portugal, Italy, Austria, Germany, and France, the Dutch have been reluctant to implement a total smoking ban in bars. The smoking ban is widely believed to reduce nicotine levels inhaled by bar workers and customers, reduce air pollution, indirectly help potential quitters move towards having a healthy lifestyle, and protect the public from potential health risks. Further, restrictions to smoking have led to a reduction in the number of individuals who smoke, provided smoke-free environments, and decreased the exposure of children and youth to advertisements encouraging smoking behavior. Although the potential benefits of the smoking ban have been established, some bar owners in The Netherlands are reluctant to follow the implementation of the ban. Reasons mentioned by bar owners for noncompliance include minimal sanctions, competitors that allowed smoking in their bar, and delayed enforcement. Reasons to comply include: if the cost for compliance were minimal, if competitors were complying, and if the implementation of law were consistent and coordinated. In this study we simulated the behavior of smoking and nonsmoking individuals with different addiction, annoyance, and intolerance levels. Using agent-based modelling our agents were initialized with these attributes either as 1 or 2 wherein 1 represented a low level and 2 a high level. In our model we simulated how a complaining behavior can enforce a social norm, such as “no smoking is allowed.” We focused on how complaining elicits obedience to accepted norms on the basis that complaining promotes normative obedience and discourages misconduct about noncompliance of smoking individuals. Secondary to this goal is the expectation that because smoking is banned in bars but may be allowed in some other bars, a segregation of groups may emerge as a consequence of sanctioning an illegal behavior in some bars but accepting it in other bars.
Keywords: Smoking; Complaints and complaining